Feared [compact disc, unabridged] - Scottoline, Lisa (Scottoline, Lisa. Rosato & DiNunzio novel., 2018)
When nemesis Nick Machiavelli targets her family with frivolous legal claims and slander that escalate to an unthinkable tragedy, Mary DiNunzio discovers her own unsettling capacity for dark retaliation.